From operculum to bead: Production of pearls from opercular bones of Cyprinus carpio in the Romanian Eneolithic. (1st October 2016) - Ma˘rga˘rit, Monica; Radu, Valentin; Popovici, Dragomir Nicolae
Abstract : Significant amounts of opercular bones from Cyprinus carpio, used to manufacture circular pearls for adornments, were found from the Romanian Eneolithic, associated with the Gumelnita culture. The origins of this raw material are local: the carp was an important food resource for the communities located close to the River Danube. An experimental program was undertaken to obtain replicas of pearls of C. carpio, to compare with the archaeological pieces, in order to identify an a chain of manufacture resulting in the finished pieces. The study of the adornments represents an inexhaustible source of reflection because, through them we can identify aspects of the human groups' symbolical behaviour, and socio-economical aspects of these communities' evolution. In this case they suggest that the aquatic world, with its resources, had an important position in the spiritual life of these communities.